Classification of Remote Sensing Data With Morphological Attribute Profiles: A decade of advances - Maia, Deise Santana; Pham, Minh-Tan; Aptoula, Erchan; Guiotte, Florent; Lefevre, Sebastien (IEEE-Inst Electrical Electronics Engineers Inc, 2021)
Morphological attribute profiles (APs) are among the most prominent methods for spatial-spectral pixel analysis of remote sensing images. Since their introduction a decade ago to tackle land cover classification, many studies have been contributed to the state of the art, focusing not only on their application to a wider range of tasks but also on their performance improvement and extension to more complex Earth observation data.
Keywords: Vegetation; Image reconstruction; Filtering; Feature extraction; Tools; Shape; Principal component analysis